Development of graphene and its electrochemical characteristics - Ang, Yan Qi (2011)
Heavy metals ions are commonly found in natural water and their presence has negative impact on the habitat as well as human health. The study of electrochemical sensors to trace metal ions is often necessary as it provides a fast, safe, direct and reliable analytical information. In this project, a simple yet inexpensive method is used to fabricate graphene layers. A Ni/C/p-Si tri-layer stack was fabricated when diamond-like carbon (DLC) or amorphous carbon layer was deposited onto Si/SiO2 substrate followed by Ni layer sputtered onto the carbon layer. The samples are thermally annealed at high temperature under an argon flow to obtain graphene coated electrodes. The graphene is characterized using Raman spectroscopy, atomic force microscopy (AFM) and high resolution transmission microscopy (HR-TEM). All the electrodes then underwent Square Wave Anodic Stripping Voltammetry (SWASV), cyclic voltammetry (CV) for surface activity tests and corrosion test to determine their relative performance in detecting lead ions (Pb2+) a buffer solution. Bismuth ions (Bi3+) were added during the tests to enhance the performance of the electrodes so as to improve the current response of Pb2+. A series of calibration curves were plotted to study the performance of the electrodes. Finally, the optimised electrode was used to detect presence of heavy metal ions in pond water to see its practicality in real life applications.